(untitled) (Research, Society and Development, 2021)
Objective: To analyze, based on the literature, the practice of physical exercise and eating habits in the elderly. Methodology: This is a theoretical essay of a reflective nature, carried out through a non-systematic bibliographic review, with a qualitative approach. Data collection was performed through an online search of articles in databases: academic google, online scientific electronic library (SCIELO), national center for information on biotechnology (NCBI) and PUBMED, using the descriptors: physical exercises, eating habits, elderly, well-being, aging, and their respective standardized translations in health sciences descriptors (DECS). As inclusion criteria for the selection of materials, the following were considered: articles in English and Portuguese, published from 2010 to 2020, available in full and whose results covered the topic of this research. Results: The literature analysis was arranged in five thematic categories, namely: Aging process; Healthy aging; Physical exercise; Quality of life of the elderly person; and, Eating habits. Final Considerations: The practice of physical exercise and healthy eating habits should be encouraged in the Elderly, in view of its proven impact on their quality of life.